Evaluation of 6 Commercial SARS-CoV-2 Serology Assays Detecting Different Antibodies for Clinical Testing and Serosurveillance. (10th May 2021) - Nicholson, Suellen; Karapanagiotidis, Theo; Khvorov, Arseniy; Douros, Celia; Mordant, Francesca; Bond, Katherine; Druce, Julian; Williamson, Deborah A; Purcell, Damian; Lewin, Sharon R; Sullivan, Sheena; Subbarao, Kanta; et al.
Abstract: Background: Serological testing for severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) complements nucleic acid tests for patient diagnosis and enables monitoring of population susceptibility to inform the coronavirus disease 2019 (COVID-19) pandemic response. It is important to understand the reliability of assays with different antigen or antibody targets to detect humoral immunity after SARS-CoV-2 infection and to understand how antibody (Ab) binding assays compare to those detecting neutralizing antibody (nAb), particularly as we move into the era of vaccines. Methods: We evaluated the performance of 6 commercially available enzyme-linked immunosorbent assays (ELISAs), including a surrogate virus neutralization test (sVNT), for detection of SARS-CoV-2 immunoglobulins (IgA, IgM, IgG), total or nAb. A result subset was compared with a cell culture–based microneutralization (MN) assay. We tested sera from patients with prior reverse transcription polymerase chain reaction–confirmed SARS-CoV-2 infection, prepandemic sera, and potential cross-reactive sera from patients with other non-COVID-19 acute infections. Results: For sera collected >14 days post–symptom onset, the assay achieving the highest sensitivity was the Wantai total Ab at 100% (95% CI, 94.6%–100%), followed by 93.1% for Euroimmun NCP-IgG, 93.1% for GenScript sVNT, 90.3% for Euroimmun S1-IgG, 88.9% for Euroimmun S1-IgA, and 83.3% for Wantai IgM. Specificity for the best-performing assay was 99.5% for the Wantai total Ab, and for the lowest-performing assay it was 97.1% for sVNT (as per the Instructions for Use [IFU]). The Wantai Total Ab had the best agreement with MN at 98% followed by Euroimmun S1-IgA, Euro NCP-IgG, and sVNT (as per IFU) with 97%, 97% and 95%, respectively; Wantai IgM had the poorest agreement at 93%. Conclusions: Performance characteristics of the SARS-CoV-2 serology assays detecting different antibody types are consistent with those found in previously published reports. Evaluation of the surrogate virus neutralization test in comparison to the Ab binding assays and a cell culture–based neutralization assay showed good result correlation between all assays. However, correlation between the cell-based neutralization test and some assays detecting Ab's not specifically involved in neutralization was higher than with the sVNT. This study demonstrates the reliability of different assays to detect the humoral immune response following SARS-CoV-2 infection, which can be used to optimize serological test algorithms for assessing antibody responses post–SARS-CoV-2 infection or vaccination.